2011
DOI: 10.1021/la200199b
|View full text |Cite
|
Sign up to set email alerts
|

Surface X-ray Scattering of Stepped Surfaces of Platinum in an Electrochemical Environment: Pt(331) = 3(111)-(111) and Pt(511) = 3(100)-(111)

Abstract: Real surface structures of the high-index planes of Pt with three atomic rows of terraces (Pt(331) = 3(111)-(111) and Pt(511) = 3(100)-(111)) have been determined in 0.1 M HClO(4) at 0.1 and 0.5 V(RHE) with the use of surface X-ray scattering (SXS). The surfaces with two atomic rows of terraces, Pt(110) = 2(111)-(111) and Pt(311) = 2(100)-(111) = 2(111)-(100), are reconstructed to a (1 × 2) structure according to previous studies. However, the surfaces with three atomic rows of terraces have pseudo-(1 × 1) str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Surface energy of the close-packed (111) structure is lower compared with other surfaces; enlargement of the (111) terrace width stabilizes the surface structure after the reconstruction to (1 © 2). 24 On the surfaces with more than 3 atomic rows of terrace, however, (111) terrace width does not increase after the (1 © 2) reconstruction. Thus enlargement of (111) terrace width is regarded as a motive force to the (1 © 2) reconstruction on single crystal electrodes of Pt.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Surface energy of the close-packed (111) structure is lower compared with other surfaces; enlargement of the (111) terrace width stabilizes the surface structure after the reconstruction to (1 © 2). 24 On the surfaces with more than 3 atomic rows of terrace, however, (111) terrace width does not increase after the (1 © 2) reconstruction. Thus enlargement of (111) terrace width is regarded as a motive force to the (1 © 2) reconstruction on single crystal electrodes of Pt.…”
Section: Introductionmentioning
confidence: 98%
“…22 However, the surfaces composed of 3 atomic rows of terrace, such as Pt(310) = 3(100)-(110), 23 Pt(511) = 3(100)-(111) and Pt(331) = 3(111)-(111), have unreconstructed (1 © 1) structures. 24 Reconstruction to (1 © 2) enlarges (111) terrace width on the surfaces with 2 atomic rows of terrace such as Pt(110) and Pt(311). Surface energy of the close-packed (111) structure is lower compared with other surfaces; enlargement of the (111) terrace width stabilizes the surface structure after the reconstruction to (1 © 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real surface structures of the high index planes of Pt were also determined using SXD in 0.1 M HClO 4 . [28][29][30] Surfaces composed of two atomic rows of terrace such as Pt(110) and Pt(311) are reconstructed to (1 © 2) structure, whereas surfaces with more than three atomic rows of terraces have unreconstructed (1 © 1) structure. 30 Interlayer spacing between the first and the second layers d 12 is expands 13% compared with the bulk on Pt(331) that is composed of 3 atomic rows of (111) terrace and monatomic height (111) step, whereas d 12 is contracted 37% on Pt(511) that consist of 3 atomic rows of (100) terrace and monatomic height of (111) step.…”
Section: Introductionmentioning
confidence: 99%
“…30 Interlayer spacing between the first and the second layers d 12 is expands 13% compared with the bulk on Pt(331) that is composed of 3 atomic rows of (111) terrace and monatomic height (111) step, whereas d 12 is contracted 37% on Pt(511) that consist of 3 atomic rows of (100) terrace and monatomic height of (111) step. 30 STM study showed that bare Pd(111) has unreconstructed (1 © 1) structure in electrochemical environments. 31 Structures of adsorbed iodine were determined on Pd(111), Pd(100) and Pd(110) in 0.05 M H 2 SO 4 using STM, 32 however, real surface structures of bare Pd(100) and Pd(110) were not known in electrochemical environments.…”
Section: Introductionmentioning
confidence: 99%